Ecological Marketing Strategies: Integrating Sustainability and Consumer Engagement for Corporate Growth and Eco-Performance - Peri Purnama (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
Background: With growing concerns over environmental degradation and climate change, businesses are increasingly adopting ecological marketing strategies to promote sustainability while enhancing corporate growth. Ecological marketing integrates environmental considerations into business practices, allowing firms to meet consumer demand for eco-friendly products and practices. However, there remains a gap in understanding how ecological marketing can be integrated with consumer engagement to improve eco-performance and drive business success. Methods: This study employs a mixed-methods approach, combining a literature review, consumer surveys, and interviews with marketing managers and sustainability officers. The literature review identifies key trends and gaps, while surveys assess consumer attitudes towards sustainability. Interviews provide insights into how companies implement green marketing strategies. The data is analysed using statistical and thematic techniques. Results: The findings indicate that ecological marketing strategies positively influence corporate growth, consumer engagement, and eco-performance. Consumers are motivated by sustainability in their purchasing decisions and are willing to support brands that align with their values. Companies that adopt green marketing strategies experience increased brand loyalty and reduced environmental impacts. Conclusions: Ecological marketing is a powerful tool for businesses to achieve growth and sustainability. However, successful integration requires transparency, innovation, and a long-term commitment to sustainability. Implications: This research offers a framework for businesses to incorporate ecological marketing into their strategies, highlighting the importance of consumer engagement in driving eco-performance. Limitations: The study is limited by its reliance on surveys and interviews, which may not fully capture sector-specific challenges or the long-term impacts of ecological marketing strategies.